Recycled concrete aggregate as a road base material - G. G., Giwangkara; A., Mohamed; N. H. A., Khalid; H. M., Nor; Mohd Rosli, Hainin; Putra Jaya, Ramadhansyah; W. N. H. M., Sani; C. R., Ismail; M. M. A., Aziz (IOP Publishing, 2019)
This conference with the theme "Overcoming Challenges of the 4th Industrial Revolution in Geotechnical Engineering" is a platform to share, discuss and disseminate recent findings, developments and advancements in geotechnical engineering in terms of theory, materials, design and applications. Referring to the theme, it is noteworthy to realize that the 4th Industrial Revolution (or 4IR) is essentially characterized by a fusion of technologies in various fields which include among other things artificial intelligence, nanotechnology and the Internet of Things (IoT). The changes and advancements in technology in the era of 4IR are evolving at a very fast pace, requiring us to respond accordingly. Hence, our responses must be integrated and comprehensive, regardless of which institutions or organisations we belong to, from the public and private sectors to academia and civil society. With the participations of academicians, researchers, engineers, inventors and designers, local and abroad, I look forward to observing and participating in harmonious and fruitful discussions as part of our efforts and preparations to keep pace with the ever-evolving changes in technology while maximizing the benefits in the field of geotechnical engineering.